The Threat Of Tax Avoidance By Multinational Companies Through Profit Shifting - Wigiana, Lira; Subanidja, Steph; Supriyadi, Edy (WIM Solusi Prima, 2024)
Tax is a mandatory contribution that taxpayers must submit to the state in accordance with the provisions of the law. However, in reality, tax avoidance by multinational companies through profit shifting has resulted in Indonesia losing tax revenue every year. Based on this, the discussion in this study is the causes of the threat of tax avoidance by multinational companies through profit shifting. This research also discusses intelligence strategies in facing the threat of tax avoidance. The method used is qualitative with data sourced from interviews and literature studies. The analysis used is Creswell analysis processed through the Nvivo application. This research also uses data source triangulation to examine data validity. Based on the research results, the causes of this threat are the intention and ability to jeopardize tax revenue. Intelligence strategies in facing this threat are a combination of intelligence objectives, intelligence methods, and intelligence resources. Intelligence objectives include state revenue, tax compliance, and Data-Based Organizations. Intelligence methods include Business Intelligence (BI), Compliance Risk Management (CRM), and data analysis. Intelligence resources include cooperation and data and information.